Diagnostic Accuracy of Electro-Chemiluminescence Immunoassay Anti-SARS-CoV-2 Serological Test - Afzal, Nayab (Cureus, 2021)
Objective: To determine the diagnostic accuracy of fully automated electro-chemiluminescence immunoassay (ECLIA) anti-SARS-CoV-2 serological test for detection of past SARS-CoV-2 infection and to be used in seroprevalence surveys. Method: A total of 426 patients who had tested for anti-SARS-CoV-2 from August 1 to 31, 2020 were selected for the study. Informed consent was obtained and a questionnaire including the patient’s age, gender, symptoms, and past polymerase chain reaction (PCR) status was filled by the patient. Samples were analyzed for anti-SARS-CoV-2 antibodies on Roche Cobas e601. Results: The mean age of the patients was 42.43±16.67 years. One hundred and five (24.6%) were PCR positive, while 321 (75.4%) were PCR negative. Most patients were males 241 (56.6%) while 185(43.3%) were females. Over 185(43.3%) patients presented with symptoms, and the rest of the patients 241 (56.6%) were asymptomatic. Anti-SARS-CoV-2 had sensitivity 89.5%, specificity 99.06%, positive predictive value (PPV) 96.90%, negative predictive value (NPV) 96.6%, and positive likelihood ratio 4.26, while negative likelihood ratio 0.1. Diagnostic accuracy of anti-SARS-CoV-2 was 96.7% based on receiver-operating characteristic (ROC) curve analysis. Conclusion: Anti-SARS-CoV-2 is very useful for the detection of past COVID-19 infection; it can be proved helpful in the identification of post-COVID complications and actual disease burden in a population.